Discrimination Of Lard And Other Edible Fats After Heating Treatments Using Partial Least Square Regression (plsr), Principal Component Regression (pcr) And Linear Support Vector Machine Regression (svmr). - Nor Aishah Mohd Salleh; Mohd Sukri Hassan (IOP Publishing Ltd., 2024)
Volume 1366 2nd International Conference on Applied & Industrial Mathematics and Statistics 23–25 July 2019, Kuantan, Pahang, Malaysia